Cutaneous reactions to pediatric cancer treatment: Part I. Conventional chemotherapy. Issue 1 (10th November 2020) - Sous, Dana; Armstrong, Amy E.; Huang, Jennifer T.; Shah, Sonal; Carlberg, Valerie M.; Coughlin, Carrie C.
Abstract: Chemotherapies often cause side effects of the skin, nails, and mucosal surfaces. These mucocutaneous toxicities contribute to morbidity and affect quality of life. Identification and management of these drug‐induced eruptions is vital to allow for continuation of essential therapies. This review demonstrates the wide range of chemotherapy‐induced cutaneous toxicities in children and includes clues for diagnosis as well as tips for counseling and management.